PEMBERDAYAAN DISABILITAS MELALUI DIGITALISASI EKONOMI KREATIF: SINERGI ASTA CITA UNTUK PEMBANGUNAN INKLUSIF DI KABUPATEN BINTAN - Ferdi Chahyadi; Risdy Absari Indah Pratiwi; Imalinda Deryane (Jurnal Pengabdian Masyarakat Multidisiplin, 2026)
Persons with disabilities have great potential in the creative economy; however, limited access to technology, training, and digital markets continues to hinder their economic independence. This community service program aims to enhance the production capacity and digital marketing skills of a group of disabled miniature craftsmen in Bintan Regency through creative economy digitalization training. The program was implemented over eight months using a participatory approach and involved 10 persons with disabilities as primary partners. The implementation methods included product standardization workshops, design software training, digital marketing, online business management, standardized production processes, application of product branding technology, as well as mentoring and evaluation to support sustainable craft production. The results indicate significant improvements in participants’ knowledge, skills, and production capacity. Average production knowledge increased by 83.7% based on pre-test and post-test results, while production skills reached an average score of 4 out of 5 based on professional assessment. In addition production capacity increased, and the digital marketing system has been fully prepared for operation, as indicated by the availability of a dedicated marketing website, active e-commerce accounts, a product logo, and official trademark registration with the Directorate General of Intellectual Property (DJKI).